Thermal taster status: Evidence of cross‐modal integration - Hort, Joanne (Hum Brain Mapp, 2016)
Thermal taster status refers to the finding that, in some individuals, thermal stimulation of the tongue elicits a phantom taste. Little is known regarding the mechanism for this, it is hypothesised to be a result of cross‐wiring between gustatory and trigeminal nerves whose receptors co‐innervate papillae on the tongue. To address this, we use functional magnetic resonance imaging to perform the first study of whether the cortical response to gustatory‐trigeminal samples is altered with thermal taster status. We study the response to cold (6°C) gustatory (sweet) samples at varying levels of trigeminal stimulation elicited by CO(2) (no CO(2), low CO(2), high CO(2)) in thermal taster (TT) and thermal non‐taster (TnT) groups, and evaluate associated behavioural measures. Behaviourally, the TT group perceived gustatory and trigeminal stimuli significantly more intense than TnTs, and were significantly more discriminating of CO(2) level. fMRI data revealed elevated cortical activation to the no CO(2) sample for the TT group compared to TnT group in taste, oral somatosensory and reward areas. In TnTs, a significant positive modulation in cortical response with increasing level of CO(2) was found across taste, somatosensory and reward areas. In contrast, in TTs, a reduced positive modulation with increasing level of CO(2) was found in somatosensory areas (SI, SII), whilst a significant negative modulation was found in taste (anterior insula) and reward (ACC) areas. This difference in cortical response to trigeminal stimuli supports cross‐modal integration in TTs, with gustatory and trigeminal nerves highly stimulated by cold gustatory samples due to their intertwined nature. Hum Brain Mapp 37:2263–2275, 2016. © 2016 Wiley Periodicals, Inc.